Efeito agudo de diferentes volumes de alongamento estático na contração voluntária máxima de idosas - Hayakawa, Marina Yumi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Several studies have shown that different stretching routines can lead to decreases on acute neuromuscular system performance. Although the deficit in muscle strength mediated by different methods of stretching has been systematically observed, few studies have investigated the possible existence of a dose-response relationship between the amount of stretching and muscle strength deficit in older adults. In this context, the objective of this study was to investigate the acute effect of two different stretching volumes on isometric force-time curve (Cf-t) in elderly women. The study included 13 older women (64.08 ± 4.27 years, 69.98 ± 10.56 kg, 157.90 ± 8.66 cm, 28.25 ± 4.22 kg/m²). The participants visited the laboratory for five consecutive days, among which the first two were used for familiarization. During the other three days the participants underwent experimental conditions: control (C) stretch 30 seconds (AE30) and stretch 60 seconds (AE60). For the AE30 and AE60 conditions, three series of passive static stretching were performed, with duration of 30 and 60 seconds, respectively. The experimental conditions were performed with an interval of at least 24 hours between them and the order of execution was randomized. The recording of isometric Cf-t of the knee extensor muscles was performed in extensor chair connected to a force transducer. Measurements were recorded immediately after each experimental condition, for five seconds. For statistical analysis, descriptive procedures were used and ANOVA one way to check possible changes on the Maximal Voluntary Contraction (CVM) and Peak Rate of Force Development (TDFP) among the three conditions (p <0.05). The ANOVA showed no statistically significant difference for CVM and TDFP, between the three conditions. It can be concluded that different volumes of static stretching, three sets ...(Complete abstract click electronic access below)

Vários estudos têm demonstrado que diferentes rotinas de alongamento podem levar a decréscimos agudos no desempenho do sistema neuromuscular. Entretanto, poucos trabalhos procuraram investigar a possível existência de uma relação doseresposta entre o volume de alongamento e o déficit de força muscular em idosos. Neste contexto, o objetivo do presente estudo foi investigar o efeito agudo de dois diferentes volumes de alongamento na curva força-tempo (Cf-t) isométrica. Participaram do estudo 13 idosas (64,08 ± 4,27 anos; 69,98 ± 10,56 kg; 157,90 ± 8,66 cm; 28,25 ± 4,22 kg/m²), que visitaram o laboratório durante cinco dias consecutivos, dentre os quais, os dois primeiros foram utilizados para familiarização. Nos três dias subsequentes as participantes foram submetidas às condições experimentais: controle (C), alongamento 30 segundos (AE30) e alongamento 60 segundos (AE60). Nas condições AE30 e AE60 foram realizadas três séries de alongamento estático passivo para o quadríceps femoral da perna dominante, de 30 e 60 segundos, respectivamente. As condições experimentais foram realizadas com intervalo de no mínino 24 horas e a ordem de execução das mesmas foi aleatorizada. O registro da Cf-t isométrica dos músculos extensores do joelho foi realizado em uma cadeira extensora conectada a um transdutor de força. As medidas foram registradas imediatamente após cada condição experimental, durante cinco segundos. Para análise estatística, foram empregados procedimentos descritivos e ANOVA one way para verificar possíveis alterações no comportamento da Contração Voluntária Máxima (CVM) e Taxa de Desenvolvimento de Força Pico (TDFP) entre as três condições (p<0,05). A ANOVA não apresentou diferença estatisticamente significativa para CVM e TDFP, entre as três condições. Concluiuse que ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Alongamento (Fisiologia); Envelhecimento; Articulações - Amplitude do movimento; Cinesiologia; Exercícios físicos; Stretch (Physiology); Aging; Joints - Range of motion; Kinesiology